Low-intensity pulsed ultrasound enhances posterior spinal fusion implanted with mesenchymal stem cells-calcium phosphate composite without bone grafting - Hui, Celine Fan Fong; Chan, Chun Wai; Yeung, Hiu Yan; Lee, Kwong Man; Qin, Ling; Li, Gang; Leung, Kwok Sui; Hu, Yun Yu; Cheng, Jack Chun Yiu (Spine (Philadelphia, Pa. 1976), 2011)
Experimental study on the effect of low-intensity pulsed ultrasound (LIPUS) on rabbit spinal fusion with mesenchymal stem cell (MSC)-derived osteogenic cells and bioceramic composite. To investigate the efficacy of LIPUS in enhancing fusion rate and bone formation with porous tricalcium phosphate (TCP) bioceramic scaffold impregnated with MSCs without any bone grafts. The goal of spinal fusion in the corrective spinal surgery for spinal deformities is to achieve solid bony fusion between selected vertebral segments. Previous studies with bone morphogenetic proteins and genetically manipulated materials revealed significant difficulties in actual clinical application. Alternative such as LIPUS has been shown to be effective in enhancing healing of fracture and nonunion clinically. Its potential for enhancing spinal fusion warrants further in-depth study. Posterolateral intertransverse processes spinal fusion at the L5 and L6 levels were evaluated in New Zealand white rabbit model. The animals were divided into three groups with (A) TCP alone, (B) TCP with differentiated MSCs, and (C) TCP with differentiated MSCs and LIPUS treatment. At week 7 postoperation, manual palpation, peripheral quantitative computed tomography, and histomorphometric assessments were performed. At week 7 postoperation, a statistically significant increase in clinical fusion by manual palpation was observed in group C animals treated with LIPUS (86%) in comparing with groups A (0%) and B (14%) without LIPUS. With peripheral quantitative computed tomographic analysis, the bone volume of group C fusion mass was significantly larger than the other two groups. Group C fusion also had better osteointegration length between host bone and implanted composite and more new bone formed in the TCP implants. Importantly, all the group C animals had osteochondral bridging--early stage of bony fusion histologically. Endochondral ossification was observed at the junction between the cartilaginous and osseous tissues at the intertransverse processes area. Quantitative analysis showed that the fusion mass in group C had significantly smaller gap and larger area of cartilaginous tissue between the transverse processes. The present study showed that the combination of synthetic biomaterials, autologous differentiated MSCs, and LIPUS could promote clinical fusion in rabbit posterior spinal fusion model. The mechanism was likely to be mediated through better osteointegration between the host bone and implanted materials and enhanced endochondral ossification at the fusion site.